ZnO and TiO2 Based Nanostructures - Andrea Lamberti (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
Nowadays, transition metal-oxides can be considered the most investigated materials especially in their nanostructured forms thanks to their intrinsic smart properties and to the positive effects induced by scaling their dimension down to the nanoscale. Among them, ZnO and TiO2 have attracted particular interest mainly because of their multi-functionality applicable in an enormous range of research fields. The present Special Issue - composed by twenty-seven papers, both reviews and research articles - covers the most recent advances in ZnO and TiO2 nanostructures, concerning not only their synthesis and characterization, but also reports of the manner(s) in which their functional and smart properties can be applied in working devices. Applications of such nanostructures can range widely, from biomedical and drug delivery devices to piezoelectric and chemical sensors, and energy harvesting, conversion, and storage devices.